Hadith #2920 - Sunan al-Nasa'i - Hajjaj bin al-Minhal حجاج بن المنهال; ibn Abbas; Ibn Jurayj ابن جريج; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
he and the Messenger of Allah entered the House, and he told Bilal to shut the door. At that time the House was built on six pillars. He waled forward until, when he was between the two columns that are on the either side of the door of the Kabah, he sat down, praised Allah, asked of him, and prayed for forgiveness. Then he god up, and went to the back wall of the Kabah, placed his face and cheek against it and praised Allah, asked of Him, and prayed for forgiveness. Then he went to each corner
Grade:

Hadith #2921 - Sunan al-Nasa'i - ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“I entered the House with the Messenger of Allah. He sat and praised Allah, and recited the Takbir, and the Tahlil. Then he went to the wall of the House that was in front of him, and placed his chest, cheek and hands on it, then he recited the Takbir, and the Tahlil, and supplicated. And he did that in all the corners, then he came out, and turned to face the Qiblah while he was in front of the door, and he said: ‘This is the Qiblah, this is the Qiblah.'”
Grade:

Hadith #3810 - Sunan al-Nasa'i - ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“They do not bring any good; they are just a means of taking wealth from the miserly.”
Grade:

Hadith #3811 - Sunan al-Nasa'i - Hajjaj bin al-Minhal حجاج بن المنهال; ibn Abbas; Ibn Jurayj ابن جريج; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“The Messenger of Allah forbade vows and said: ‘They do not change anything; they are just a means of taking wealth from the miserly.'”
Grade:

Hadith #5650 - Sunan al-Nasa'i - Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; ibn Mas'ud; Ibrahim bin Sa'id al-Juhari إبراهيم بن سعيد الجوهري; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول (Sunan al-Nasa'i)
“Mu’adhah narrated to me from ‘Aishah, that the Messenger of Allah forbade Nabidh made in An-Naqir, Al-Muqayyar, Ad-Dubba’, and Al-Hantam.” And in the narration of Ibn ‘Ulayyah, Ishaq said: “And Hunaidah mentioned from ‘Aishah similar to the narration of Mu’adhah, and she named earthenware containers. I said to Hunaidah: ‘Did you hear her say earthenware containers?’ She said: ‘Yes.'”
Grade:

Hadith #3028 - Sunan Abi Dawud - ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول (Sunan Abi Dawud)
Abyad spoke to the Messenger of Allah (ﷺ) about sadaqah when he came along with a deputation to him. He replied: O brother of Saba’, sadaqah is unavoidable. He said: We cultivated cotton, Messenger of Allah. The people of Saba’ scattered, and there remained only a few at Ma’arib. He therefore concluded a treaty of peace with the Messenger of Allah (ﷺ) to give seventy suits of cloth, equivalent to the price of the Yemeni garments known as al-mu’afir, to be paid every year on behalf of
Grade: Da'if

Hadith #1416 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; ibn Abbas; Sufyan bin 'Uyaynah سفيان بن عيينة; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: “The Messenger of Allah (ﷺ) had cupping done when he was fasting and in Ihram.”
Grade: